Cuarteto del dinero - Bueno Ochoa, Luis (Miscelánea Comillas, 2011)
This paper is an approach to the concept of money through four ways: philosophical, reverential, immortal and, finally, forth is based on avarice. Variousauthors such us Simmel, Maeztu and Goethe, among others, support the dissertation.